Productive Development Policies in Costa Rica: Market Failures, Government Failures, and Policy Outcomes - Ricardo Monge-Gonzalez; Luis Rivera; Julio Rosales-Tijerino (Inter-American Development Bank (IDB), 2010)
This paper analyzes five Productive Development Policies (PDPs) implemented in Costa Rica, finding that they are not optimally addressing market failures. Moreover, government failures rather than market failures represent the main justification for PDPs. Even in the presence of market failures, the policy instruments applied are not necessarily the most economically efficient but rather the most politically feasible options. In addition, the lack of policy evaluation and monitoring prevents adjustments and corrections of such policies. Addressing the arguments for policy intervention and incorporating the results of evaluation into policy design and reform are necessary conditions for success. In spite of positive policy outcomes, limitations to enhance competitiveness and create the conditions for productivity growth are still present. An umbrella approach in the case of those PDPs that reinforce each other is necessary for productivity growth.
Keywords: L52; D78; 330; Policy Analysis; Policy Making; Industrial Policy; Costa Rica